Um olhar frankfurtiano sobre o alcance da programação esportiva da televisão nas aulas de educação física escolar - Poit, Davi Rodrigues (2008)
The aim of this research is to analyze the reach of TV sports programs on physical education classes in schools, specifically under the perspective of the broadcasting of major sport events such as Olympic Games, Pan American Games, soccer championships and others. As theoretical reference, it was considered the first generation of the school of Frankfurt, especially T.W. Adorno and M. Horkheimer. The study privileged the analysis of the cultural industry concepts, identification and competition. Empirical research was carried out in a traditional private school in the city of Jundiaí in São Paulo state - Brazil, with 53 students of the second year of high school (16 years old). The research aimed: 1 - To verify the frequency with that the students attend the main sporting events of television and activities that can have effect in their formation. 2 - To verify the adhesion to sports programs on TV. 3 - To verify if the adhesion to the sport programs on TV promotes the identification of the spectators with the athletes who are put in the headlines by the media. 4 - To verify if the sport programs on TV triggers competitive tendencies on the behaviour of the students who watch them. 5 - If there is a correlation among the adhesion to the cultural industry, identification and competition. The data was obtained from questionnaires and scales organized and tested for the specific purpose. After analyzing the data, constructing tables/charts and doing statistics tests, the results showed how the sports programs on TV, specially the cultural industry as a system, has an effect on the attitude building, comprehension and behavior of students during the physical education classes. The results did not allow us to confirm the totality of hypothesis presented. However they indicate that the pertinence of the cultural industry concept and that its ideology gets to schools. The dynamics carried out with videos show that there is a considerable influence from the media on the behavior of students during the classes of Physical Education in school. The tests sperman did not indicate correlation among the adhesion to the cultural industry, identification and competition. Thus, with the growth of the sports industry and consequent support of TV to the spectacle-sport, there is belief that this theme will encourage other research aiming to understand better their effects on physical education classes in schools and its implications on the formation of the being